A Study of types and core constituents of Acehnese relative clauses - Denni Iskandar; Mulyadi Mulyadi; Khairina Nasution; Ridwan Hanafiah (Studies in English Language and Education, 2021)
This research aims to determine and explain the types and the core constituents of Acehnese relative clauses which so far have not been thoroughly discussed. To collect data for this study, a direct elicitation technique is used, and the data is then analyzed through a qualitative descriptive technique. The results showed that the relative clauses in Acehnese were clauses embedded as modifiers of noun phrases. Similar to the relative clauses’ theory proposed by experts in the Acehnese, there are five types of relative clauses: relativization of subject, relativization of predicate, relativization of object, relativization of possessive, and relativization of noun. Relative clauses in Acehnese are formed by connecting core nouns and relative clauses through the connecting word ‘nyang’, except for the relative clause of the predicate element through the ellipsis of the predicate element. The basic structure of the Acehnese relative clauses is the arrangement of the main constituents preceding (postnominal) the relative clauses. The constituents that described the relative clauses could form words or phrases depending on the reference to the meaning of the relative clauses. In the Acehnese, the following elements do not exist: (1) relative clauses that can be reduced by adverbials such as in English, (2) relative pronouns as in German and relative particles such as in Chinese Mandarin; and (3) the attachment of relative suffixes to verbs as in Korean.